Analyzing the Impact of Brand Credibility on Consumer Purchase Intention in the Kurdistan Region of Iraq (KRI) (Academic Journal of International University of Erbil, 2025)
A major determinant of customer purchase intention is brand credibility, which shapes how customers assess a brand's overall value, trustworthiness, and quality. Therefore, the main objective of this study is to examine the influence of brand credibility on customer purchase intentions. To achieve this, a quantitative technique based on convenience sampling was employed. A total of 501 online surveys were gathered from individuals across four governorates (Erbil, Duhok, Sulaymaniyah, and Halabja) in the Kurdistan Region of Iraq (KRI). Simple Linear Regression, Pearson Correlations, and (SEM) Structural Equation Modeling were used to either confirm or reject the study's hypotheses. The main results revealed that, among the three dimensions of brand credibility, attractiveness has a significant impact on consumers' intentions to make purchases, followed by trustworthiness and expertise. By concentrating their branding and marketing efforts on three dimensions—attractiveness, trustworthiness, and expertise—businesses may effectively increase customer purchase intentions and develop a reputable brand image and consumer loyalty. This comprehensive strategy not only cultivates a robust brand identity but also enhances consumer trust, promotes favorable word-of-mouth, and enables sustained market expansion.